KUALITAS KIMIA DAN ORGANOLEPTIK BURGER IKAN TUNA YANG DISUBTITUSI DENGAN TEPUNG BUAH MENGKUDU (Morinda citrifolia) - Evi Huzaibah; Asrawaty Asrawaty; Minarny Gobel (Fakultas Pertanian Universitas Alkhairaat Palu, 2018)
The purpose of this research is to know the effect of addition of noni flour as substitution of tapioca flour to protein content, moisture content, and ash content and organoleptic nature of tuna burger. This study used Completely Randomized Design (RAL) and Randomized Block Design (RAK). The experimental treatment were: B1 (0% noni flour + 15% tapioca flour), B2 (2.5% noni flour + 12.5% tapioca flour), B3 (5% noni flour + 10% tapioca flour), B4 7.5% noni flour + 7.5% tapioca flour). To know the effect of treatment, then the analysis of variance and if the treatment has real effect continued with BNT advanced test. Based on the result of the research, it can be concluded that the addition of noni flour as substitution of tapioca flour to 7.5% can increase the protein tuna burger protein by 14.87%, moisture content 71.07% and ash content 2.07%, and aroma, taste, color, and texture are relatively the same on all treatments